Regulatory agencies, pharmaceutical information and the Internet: a European perspective - Bauschke, Rafael (Health policy, 2012)
The Internet facilitates access to health information and can therefore support the effectiveness of healthcare provision and empower patients in healthcare decisions. In the field of pharmaceutical therapy the electronic provision of information can improve compliance and strengthen the general understanding of pharmaceutical risks and benefits. Current political developments in Europe encourage a stronger role of the pharmaceutical industry in this regard. In light of potential conflicts inherent to the private provision of information and given their public health mandate, regulatory bodies in the pharmaceutical sector may represent an important alternative source of information. The explorative analysis in this paper reviews the websites of European pharmaceutical regulatory agencies regarding the usability and provision of information from a Layman's perspective. It is found that while the majority of agencies do provide product-related information, the usability of websites from the lay perspective is subject to variation. The reluctant position of agencies can be attributed to sectoral path dependencies, the regulatory approach and a lack of regulatory resources.
Received 24 April 2011, Revised 10 July 2011, Accepted 17 October 2011, Available online 17 November 2011
Gesehen am 13.11.2018